HAS-BLED vs. ORBIT scores in anticoagulated patients with atrial fibrillation: A systematic review and meta-analysis - Liu, Xuyang; Wang, Shengnan; He, Wenfeng; Guo, Linjuan (Frontiers in Cardiovascular Medicine, 2023)
Background The 2021 UK National Institute for Health and Care Excellence guidelines tend to recommend the ORBIT score for predicting bleeding risk in patients with atrial fibrillation (AF) with anticoagulants. Herein, we comprehensively re-assessed the predicted abilities of the HAS-BLED vs. ORBIT score since several newly published data showed different findings. Methods We comprehensively searched the PubMed electronic database until December 2021 to identify relevant studies reporting the ORBIT vs. HAS-BLED scores in anticoagulated patients with AF. Their predicted abilities were assessed using the C-index, reclassification, and calibration analysis. Results Finally, 17 studies were included in this review. In the pooled analysis, the ORBIT score had a C-index of 0.63 (0.60–0.66), 0.59 (0.53–0.66), and 0.57 (0.48–0.67) for major bleeding, any clinically relevant bleeding, and intracranial bleeding, respectively, while the HAS-BLED score had a C-index of 0.61 (0.59–0.63), 0.59 (0.56–0.63), and 0.57 (0.51–0.64) for major bleeding, any clinically relevant bleeding, and intracranial bleeding, respectively. There were no statistical differences in the accuracy of predicting these bleeding events between the two scoring systems. For the outcome of major bleeding, the subgroup analyses based on vitamin K antagonists vs. direct oral anticoagulants suggested no differences in the discrimination ability between the HAS-BLED and ORBIT scores. Reclassification and calibration analyses of HAS-BLED vs. ORBIT should be further assessed due to the limited and conflicting data. Conclusion Our current findings suggested that the HAS-BLED and ORBIT scores at least had similar predictive abilities for major bleeding risk in anticoagulated (vitamin K antagonists or direct oral anticoagulants) patients with AF, supporting the use of the HAS-BLED score in clinical practice.